Characteristics of Change Management in Transformative Islamic Education: A Multi-Site Study of Rural Private Madrasahs - Abas Shofwan; Binti Maunah; Asrop Syafi'i (Al-Marsus : Jurnal Manajemen Pendidikan Islam, 2026)
Rural private madrasahs face multiple challenges, including limited resources, declining student enrollment, and increasing competition among educational institutions. Although change management in Islamic education has been widely explored, studies focusing on the context of rural private madrasahs remain limited. This study aims to examine the characteristics of transformative change management in Islamic education through a multi-site study conducted at three rural private madrasahs in Kediri Regency, Indonesia. A qualitative approach with a multi-site research design was employed. Data were collected through interviews, observations, and document analysis and analyzed using the processes of data collection, data reduction, data verification, and conclusion drawing. The cross-site analysis revealed that transformative change management in Islamic education exhibits relatively consistent characteristics across the three madrasahs. These characteristics include transformational leadership grounded in Islamic values, collaborative human resource development, an integrative curriculum, a religious and adaptive organizational culture, and institutional partnerships. Although each madrasah implemented different strategic approaches, the change process was gradual, participatory, and directed toward strengthening educational quality while reinforcing Islamic values. The novelty of this study lies in the development of a value-based transformative change management model synthesized from cross-site findings. This model contributes to the advancement of Islamic education change management theory and provides practical guidance for the sustainable development of rural private madrasahs.